Importância do exercício físico recreativo na infância sobre o número das células progenitoras endoteliais - Souza, Livia Victorino de [UNIFESP] (2017)
Cardiovascular diseases (CVD) are the leading causes of death in the world. Characterized by morphofunctional changes in the arteries defined by changes in the stiffness, thickness and decrease of the lumen of the vessel, as well as the atherosclerotic process and the formation of the atheroma plaque that give rise to adverse cardiac events. In addition, it is clear in the literature that the atherosclerotic process is a result of natural aging. What's more, the key to these cardiovascular changes that occur from birth to death of the individual is endothelial function. In this sense, some recent studies in the literature have shown that the development of cardiovascular diseases begins in the childhood period as a result of the natural development of the individual associated with endogenous and exogenous factors. It is therefore important to develop strategies to prevent CVD during childhood. Considering that it is important that physical exercise is a playful and functional practice for children, it is important to evaluate whether recreational physical exercise is capable of promoting the benefits observed in response to physical training. Thus, the present study evaluated the effects of 10 weeks of recreational physical exercise in healthy children on the number of circulating endothelial progenitor cells. For that, 74 children were evaluated. Anthropometric assessments of physical abilities and biomarkers of endothelial function (VEGF-A, NO, MMP-9 and MMP-2) were performed. In addition, we evaluated endothelial progenitor cells (EPCs) by flow cytometry (triple labeling, CD34 / CD133 / CD309 and CD34 / CD133 / CD45) and cell culture (colony forming units). After 10 weeks of recreational physical exercise, there was a significant reduction of body weight, increase of lean mass, muscle strength and flexibility. Endothelial biomarkers VEGF-A, NO, MMP-9 showed a significant increase. Regarding CPEs, a significant increase in number and efficiency was observed. Therefore, with the data obtained in the present study we can conclude that recreational physical exercise was able to increase the number of CPEs, in addition to improving metabolic, anthropometric and physical fitness parameters and, consequently, to reduce cardiovascular risks in healthy children.